2010
DOI: 10.1007/s10342-010-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of harvest residues, fertilisers and N-fixing plants on growth and nutritional status of young Eucalyptus globulus plantations, under Mediterranean conditions

Abstract: Growth and nutritional status of young plants of Eucalyptus were assessed in a field trial, under different scenarios of harvest residue management and nutrient availability. Treatments were as follows: incorporation of harvest residues into the soil by harrowing (I); I with N fertiliser application (IF); I with leguminous, Lupinus luteus L., seeding (IL); removal of harvest residues (R); R with N fertiliser application (RF); R with leguminous seeding (RL); distribution of harvest residues on the soil surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
4
5
0
Order By: Relevance
“…At short term, harrowing led to a decrease in soil bulk density and therefore to an alleviation of soil compaction, following results reported by Madeira et al (1989Madeira et al ( , 2010 for the effects of harrowing regarding forest plantations installation. The short-term recover of higher values of soil bulk density may be associated with the low soil organic C content and the low amount of understory (lower than in the C and F treatments), which are the major factors to maintain or enhance low soil bulk density, as reported by Celette et al (2005).…”
Section: Soil Qualitysupporting
confidence: 73%
See 3 more Smart Citations
“…At short term, harrowing led to a decrease in soil bulk density and therefore to an alleviation of soil compaction, following results reported by Madeira et al (1989Madeira et al ( , 2010 for the effects of harrowing regarding forest plantations installation. The short-term recover of higher values of soil bulk density may be associated with the low soil organic C content and the low amount of understory (lower than in the C and F treatments), which are the major factors to maintain or enhance low soil bulk density, as reported by Celette et al (2005).…”
Section: Soil Qualitysupporting
confidence: 73%
“…These results are in agreement with those reported from an experimental trial in which optimum fertiliser application for a 6-year period only slightly increased tree growth (Pereira et al 1994) and from another experiment in which total removal of organic residues (forest floor litter layer and harvest residues) did not significantly affect tree growth (Madeira et al 2004). Also, similar results were observed with heavy fertiliser application during the first 3 years after planting in the presence or absence of harvest residues (Madeira et al 2010). This trend has been associated with the Mediterranean climate conditions (dry sub-humid), which determine that tree productivity is strongly affected by water availability and, at lower extent, by nutrients (Pereira et al 1994).…”
Section: Tree Growthsupporting
confidence: 71%
See 2 more Smart Citations
“…If harvesting residues are left on the soil, nutrient removal is reduced, and they also help protect against soil erosion. Even though recent studies have shown that, for Mediterranean conditions, retaining harvest residues on the soil surface does not increase tree growth compared with removing it (Jones et al 1999, Madeira et al 2010, only the incorporation of harvest residues, despite the negative effects caused by harrowing, show a positive effect on tree growth (Madeira et al 2010). In turn, bioenergy plantations (Source Energy ) were assumed to be more intensively managed than pulp stands (see Table A.2 in the Appendix) based on the type of management practiced for willow (Salix sp.)…”
Section: Discussionmentioning
confidence: 99%